Comparative evaluation of MSW incineration leachate treatment by heterogeneous catalytic O3 and UV/O3: The unexpected contribution of high salinity and overlooked role of excited state - Zhiwei Zhao; Pengfei Gan; Chengjun Zhu; Yunyi Li; Liu, Wen; Meiping Tong; Jiangyu Ye; Jialiang Liang (Chemosphere, 2022)
The efficiency and mechanism of heterogeneous catalytic O3 and UV/O3 for municipal solid waste (MSW) incineration leachate advanced treatment was systematically compared. Prior to comparison, catalyst used in heterogenous catalytic O3 and operation parameters for each technology were optimized. The COD removal of CuO@Al2O3/O3 under its optimal parameters was 57.2%, which failed to meet the standard (≥75%). In contrast, the COD removal by UV/O3 could be 82.3%. The superior efficiency of UV/O3 over CuO@Al2O3/O3 could be summarized into three aspects: (I) Cu bounded ·OH (≡Cu–O·) preferentially attacked hydrophilic groups, while free hydroxyl radical (·OH) was non-selective, thus UV/O3 exhibited a unique three-stage mechanism; (II) The oxidation potential of ≡Cu–O· was higher than that of ·OH, therefore was more vulnerable to the negative effect of radical self-quenching; (III) The existence of UV-induced excited states made organics in UV/O3 more active than in CuO@Al2O3/O3 system, thus high concentration of anions enhanced COD removal in UV/O3 but affected that in CuO@Al2O3/O3. The study further revealed the characteristics of heterogeneous catalytic O3 and UV/O3, and UV induced excited state should be considered in UV-based advanced oxidation processes (AOPs).
Keywords: Excited state; Hypersaline wastewater; Incineration leachate; Municipal solid waste; ozone